Analisis Perceived Quality Dan Perceived Value Terhadap Intention To Subscribe Pada Layanan Video On Demand Viu - Dini Kartika; Komariah, Kokom; Z, Faizal Mulia (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
R Research aim: This research aimed to determine the effect of perceived quality and value on the Intention to subscribe. Design/Methode/Approach: Quantitative method with survey research model Research Finding: The results of the study show that perceived quality and perceived value have a significant effect on intention to subscribe Theoretical contribution/Originality: This study shows that perceived quality and perceived value are very effective in making subscription decisions for video-on-demand applications Practitioner/Policy implication: Perceived quality and perceived value play a role in increasing subscription interest. To increase interest in subscribing, companies must improve the quality of features in the application. Research limitation: Variable selection only uses two independent variables: perceived quality and value.